Keabsahan Perjanjian Sewa Secara Lisan Dan Oper Sewa Tanpa Izin Pemberi Sewa - Anneu Frameswari Hidayat; Riky Rustam (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The validity of the transfer of rent in a lease agreement against the leased object without the owner's knowledge is an action that cannot be justified by law. The Lease Agreement is one type of agreement regulated in the civil code. Lease - Renting is a form of legal relationship that regulates two parties, where one party binds himself to provide the other party with the enjoyment of an item, for a specified time with the payment of a price by the last party that he agrees to. In connection with this, the background to the transfer of rent against the leased object without the knowledge of the leased object. The purpose of this study is to determine the things that cause the transfer of leased objects without the knowledge of the original owner which turns out to be a mixture of third parties. The research typology used in this study is normative legal research. The results of this study are that there has been interference from a third party or a party outside the lease agreement, related to the leased place (object), namely a kiosk used by the tenant as a place of business for the UII Jakal penyetan food stall, which has been rented by the tenant with the previous owner, the third party feels that the tenant's business is disturbing his business so that he urges the tenant to immediately move and make an agreement to transfer the kiosk lease object to him without the owner's knowledge, and the third party is the owner of Warmindo and the third party is the tenant's brother-in-law. The legal recommendation that can be given is that the third party is responsible for compensating for the losses for their actions and the dispute that occurs between the parties, the owners can be resolved amicably because the parties are still related by family ties, if the dispute cannot be resolved then it can be resolved through mediation until the dispute is resolved through litigation in court. If the parties are deemed unable to pay for the legal services of a lawyer, then the parties can request legal assistance through the Law Center Institution which provides free legal assistance and provides voluntary assistance to the parties by directing the things that must be done during the dispute resolution process, especially during the trial in court.